Describing the Diapause-Preparatory Proteome of the Beetle Colaphellus bowringi and Identifying Candidates Affecting Lipid Accumulation Using Isobaric Tags for Mass Spectrometry-Based Proteome Quantification (iTRAQ) - Tan, Qian-Qian; Liu, Wen; Zhu, Fen; Lei, Chao-Liang; Hahn, Daniel A.; Wang, Xiao-Ping (Frontiers in Physiology, 2017)
Prior to entering diapause, insects must prepare themselves physiologically to withstand the stresses of arresting their development for a lengthy period. While studies describing the biochemical and cellular milieu of the maintenance phase of diapause are accumulating, few studies have taken an ‘omics’ approach to describing molecular events during the diapause preparatory phase. We used isobaric tags and mass spectrometry (iTRAQ) to quantitatively compare the expression profiles of proteins identified during the onset of diapause preparation phase in the heads of adult female cabbage beetles, Colaphellus bowringi. A total of 3,175 proteins were identified, 297 of which were differentially expressed between diapause-destined and non-diapause-destined female adults and could therefore be involved in diapause preparation in this species. Comparison of identified proteins with protein function databases shows that many of these differentially expressed proteins enhanced in diapause destined beetles are involved in energy production and conversion, carbohydrate metabolism and transport, and lipid metabolism. Further hand annotation of differentially abundant peptides nominates several associated with stress hardiness, including HSPs and antioxidants, as well as neural development. In contrast, non-diapause destined beetles show substantial increases in cuticle proteins, suggesting additional post-emergence growth. Using RNA interference to silence a fatty acid-binding protein that was highly abundant in the head of diapause-destined females prevented the accumulation of lipids in the fat body, a common product of diapause preparation in this species and others. Surprisingly, RNAi against the fatty acid-binding protein also affected the transcript abundance of several heat shock proteins. These results suggest that the identified differentially expressed proteins that play vital roles in lipid metabolism may also contribute somehow to enhanced hardiness to environmental stress that is characteristic of diapause.